2017
DOI: 10.1186/s11671-017-2292-5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Novel 64Cu-Labeled Theranostic Gadolinium-Based Nanoprobes in HepG2 Tumor-Bearing Nude Mice

Abstract: Radiation therapy of liver cancer is limited by low tolerance of the liver to radiation. Radiosensitizers can effectively reduce the required radiation dose. AGuIX nanoparticles are small, multifunctional gadolinium-based nanoparticles that can carry radioisotopes or fluorescent markers for single-photon emission computed tomography (SPECT), positron emission tomography (PET), fluorescence imaging, and even multimodality imaging. In addition, due to the high atomic number of gadolinium, it can also serve as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Another potentially interesting local administration is intraperitoneal (i.p.) delivery as recently shown by an independent study of Hu et al in a hepatocellular carcinoma model 51 ( Figure 5B ). The biodistribution of the AGuIX NPs has been assessed after radiolabelling by 64 Cu and animals sacrificing 9, 21 and 40 h after i.p.…”
Section: Biodistribution and Pharmacokineticsupporting
confidence: 79%
See 1 more Smart Citation
“…Another potentially interesting local administration is intraperitoneal (i.p.) delivery as recently shown by an independent study of Hu et al in a hepatocellular carcinoma model 51 ( Figure 5B ). The biodistribution of the AGuIX NPs has been assessed after radiolabelling by 64 Cu and animals sacrificing 9, 21 and 40 h after i.p.…”
Section: Biodistribution and Pharmacokineticsupporting
confidence: 79%
“…AGuIX NPs have already shown their efficiency as a radiosensitizer for different in vivo preclinical models of cancer (glioblastoma, 29 , 33,40 brain metastases, 16 melanoma, 1 pancreatic cancer, 46 , 66 liver cancer, 51 chondrosarcoma, head and neck cancer 50 and lung cancer 49 ) ( Figure 10 ). A particular attention has been paid to tumours of the CNS with studies on 9L gliosarcoma bearing rats and B16F10 melanoma brain metastases bearing mice.…”
Section: Radiosensitizationmentioning
confidence: 99%
“…In order to study the radiosensitization effect of AGuIX on HCC RT, we next irradiated HepG2 cells. Our previous research showed that AGuIX can be taken up into the HepG2 cytoplasm and has a good dispersion shape in HepG2 cells, indicating that AGuIX was stable in the cells (Hu et al, 2017). The obtained of radiation dose enhancement studies in HepG2 cells (Figure 1) are similar to that by Porcel et al in pancreatic cancer cells (Detappe et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous research confirmed AGuIX uptake in the HepG2 cells and defined their biodistribution and pharmacokinetics in HepG2 tumor-bearing nude mice. This also indicated that the AGuIX accumulates in the HepG2 xenografts (Hu et al, 2017). Here, we evaluated the radiosensitization effect of AGuIX on HepG2 cells in vitro and performed MRI-guided RT using AGuIX radiosensitizer.…”
Section: Introductionmentioning
confidence: 91%
“…Several phases I clinical trials are ongoing in patients with brain metastases (NCT02820454) to enhance the sensitization of brain metastatic tumor cells to radiation . Also, AGuIX nanoparticles also have the potential to treat cervical and liver cancer . The safety, tolerability of doses of AGuIX in combination with radiation and CDDP‐based chemotherapy in patients with locally advanced cervical cancer are being evaluated in phase 1 clinical trials (NCT03308604).…”
Section: The Clinical Translation Of Nanomaterial‐mediated Tumor Radimentioning
confidence: 99%